Kapitalisme dalam Kerlingan Negara-Berdaulat: Ulasan Historis Singkat dari Era Imperium Romawi Agung sampai Era Neoliberal - Polimpung, Hizkia Yosie (Global: Jurnal Politik Internasional, 2013)
Is State in capitalism, as endlessly muttered by Marxists of all stripes, nothing more than just a committee for managing the common affairs of the whole bourgeoisie? The article rebuts this by presenting a brief evolution of the constitution of Westphalian sovereign state, one that is still reigning up to present day. It tries to distill the logic of sovereignty and shows how the State is actually operate outside the logic of the capitalism. In so doing, the article also discusses the encounter of these two logics in the liberal conceptions of state (esp. Social Democratic & Neoliberalism) along with its democratic ideology. The main point this article seeks to advance is that it is important to clarify and distinguish the two logics in order to see the inherent incompatibility that forever drives this collaboration towards crisis.